Engendering taxi-driving in Singapore : a study on gender & technology - Yeo, Jason Wei Ling (2014)
As the world becomes more technologically embedded, it is often easy to overlook the dynamics beneath interactions with technology. Using the taxi-driving as a site to study the gender-technology relationship, this paper argues how technology and the Singapore society are mutually constitutive, with technology being both source and consequence of a patriarchal gender order. Drawing from the technofeminist perspective, the ways in which notions of masculinity and femininity are embedded in and are constructed through technology will be explored. In particular, the ways in which the patriarchal gender order is materialised in, and is in turn given meaning and reinforced through technology will be presented. It will be argued how beneath the changing social network touted as emancipatory lies a persistent patriarchal ideology. Ultimately, this paper seeks to understand the gender-technology relations as well as notions of agency in the Singaporean context.